Microglial Interactions with Synapses Are Modulated by Visual Experience - Tremblay, Marie-Ève (Public Library of Science, 2010)
Microglia are the immune cells of the brain. In the absence of pathological insult, their highly motile processes continually survey the brain parenchyma and transiently contact synaptic elements. Aside from monitoring, their physiological roles at synapses are not known. To gain insight into possible roles of microglia in the modification of synaptic structures, we used immunocytochemical electron microscopy, serial section electron microscopy with three-dimensional reconstructions, and two-photon in vivo imaging to characterize microglial interactions with synapses during normal and altered sensory experience, in the visual cortex of juvenile mice. During normal visual experience, most microglial processes displayed direct apposition with multiple synapse-associated elements, including synaptic clefts. Microglial processes were also distinctively surrounded by pockets of extracellular space. In terms of dynamics, microglial processes localized to the vicinity of small and transiently growing dendritic spines, which were typically lost over 2 d. When experience was manipulated through light deprivation and reexposure, microglial processes changed their morphology, showed altered distributions of extracellular space, displayed phagocytic structures, apposed synaptic clefts more frequently, and enveloped synapse-associated elements more extensively. While light deprivation induced microglia to become less motile and changed their preference of localization to the vicinity of a subset of larger dendritic spines that persistently shrank, light reexposure reversed these behaviors. Taken together, these findings reveal different modalities of microglial interactions with synapses that are subtly altered by sensory experience. These findings suggest that microglia may actively contribute to the experience-dependent modification or elimination of a specific subset of synapses in the healthy brain.